Acoustic communication in a noisy world: can fish compete with anthropogenic noise? - Radford, A. N.; Kerridge, E.; Simpson, S. D. (Behavioral ecology, 2014)
Anthropogenic (man-made) noise has changed the acoustic environment both on land and underwater and is now recognized as a pollutant of international concern. Increasing numbers of studies are assessing how noise pollution affects animals across a range of scales, from individuals to communities, but the topic receiving the most research attention has been acoustic communication. Although there is now an extensive literature on how signalers might avoid potential masking from anthropogenic noise, the vast majority of the work has been conducted on birds and marine mammals. Fish represent more than half of all vertebrate species, are a valuable and increasingly utilized model taxa for understanding behavior, and provide the primary source of protein for >1 billion people and the principal livelihoods for hunderds of millions. Assessing the impacts of noise on fish is therefore of clear biological, ecological, and societal importance. Here, we begin by indicating why acoustic communication in fish is likely to be impacted by anthropogenic noise. We then use studies from other taxa to outline 5 main ways in which animals can alter their acoustic signaling behavior when there is potential masking due to anthropogenic noise and assess evidence of evolutionary adaptation and behavioral plasticity in response to abiotic and biotic noise sources to consider whether such changes are feasible in fish. Finally, we suggest directions for future study of fish acoustic behavior in this context and highlight why such research may allow important advances in our general understanding of the impact of this global pollutant.